School Entry Age and Children's Social-Behavioral Skills: Evidence From a National Longitudinal Study of U.S. Kindergartners. (September 2015) - Datar, Ashlesha; Gottfried, Michael A.
Prior research evaluating school entry age effects has largely overlooked the effects on social-behavioral skills despite the growing recognition of returns to such skills. This study is the first to examine the effects of kindergarten entry age on children's social-behavioral outcomes using 9 years of panel data on a national sample of U.S. children. We leverage exogenous variation in birth dates and kindergarten entrance age policies to estimate instrumental variables models. Our results show that entering kindergarten a year later is associated with significantly better social-behavioral outcomes during elementary school. However, these effects largely disappear by the end of middle school. Larger gains over time among younger entrants support the notion that the estimated effects are age-at-test effects.